2021
DOI: 10.1177/00033197211042494
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Prognosis of Peripheral Artery Disease Treatments Associated With Diabetes: A Comprehensive Meta-Analysis

Abstract: Many studies have investigated the influence of diabetes mellitus (DM) on outcomes in patients with peripheral artery disease (PAD). We performed a meta-analysis of the outcomes of PAD treatments in DM patients compared with those without DM. Long-term mortality was the primary endpoint. Secondary endpoints were in-hospital/30-day mortality, primary/secondary patency, amputation, and limb salvage. Thirty-one studies reporting 58113 patients were eligible for enrollment. The mean follow-up duration ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“… 28 In accordance, presence of DM in PAD patients resulted in a 67% increase of long‐term mortality in a recently published meta‐analysis. 29 The present findings also confirm a prior German study on data of a large health incurrence company in which the time period within 2009–2011 was analyzed. 30 Similar to our results, Richter et al identified DM as a substantial risk factor for morbidity and mortality in patients with PAD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 28 In accordance, presence of DM in PAD patients resulted in a 67% increase of long‐term mortality in a recently published meta‐analysis. 29 The present findings also confirm a prior German study on data of a large health incurrence company in which the time period within 2009–2011 was analyzed. 30 Similar to our results, Richter et al identified DM as a substantial risk factor for morbidity and mortality in patients with PAD.…”
Section: Discussionsupporting
confidence: 90%
“…An Austrian study revealed a 2.5‐fold elevated risk for death within 10 years in patients with PAD and DM compared to nondiabetic PAD patients 28 . In accordance, presence of DM in PAD patients resulted in a 67% increase of long‐term mortality in a recently published meta‐analysis 29 . The present findings also confirm a prior German study on data of a large health incurrence company in which the time period within 2009–2011 was analyzed 30 .…”
Section: Discussionsupporting
confidence: 89%
“…Further, PAD patients with DM are more likely to receive major and minor amputations compared to patients without DM [ 15 ]. In a recent meta-analysis including more than 58,000 PAD patients from 31 studies, DM was associated with a 67% elevated long-term mortality [ 16 ]. While temporal trend analysis revealed a decrease of symptomatic PAD incidence and prevalence in the general population [ 8 ], a Canadian study found no decrease of PAD-associated hospitalizations between 2006 and 2019 in people with diabetes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis including 31 studies with 58 113 patients recently compared the outcomes after LEAD treatment in diabetic patients with those without diabetes. 6 For a mean follow-up duration ranging from 1 to 89 months, diabetes was significantly associated with long-term mortality (relative risk (RR) = 1.67; 95% confidence interval (CI), 1.43–1.94; P < .001). 6 Diabetes was also significantly associated with lower primary and secondary patency.…”
mentioning
confidence: 99%
“…6 For a mean follow-up duration ranging from 1 to 89 months, diabetes was significantly associated with long-term mortality (relative risk (RR) = 1.67; 95% confidence interval (CI), 1.43–1.94; P < .001). 6 Diabetes was also significantly associated with lower primary and secondary patency.…”
mentioning
confidence: 99%